Mechanistic insights into the dual role of CCAR2/DBC1 in cancer - Hwa Jin Kim; Sue Jin Moon; Jeong Hoon Kim (Experimental and Molecular Medicine, 2023)
Abstract Cell cycle and apoptosis regulator 2 (CCAR2), also known as deleted in breast cancer 1 (DBC1), has been recently identified as a master regulator of transcriptional processes and plays diverse roles in physiology and pathophysiology, including as a regulator of apoptosis, DNA repair, metabolism, and tumorigenesis. CCAR2 functions as a coregulator of various transcription factors and a critical regulator of numerous epigenetic modifiers. Based on its ability to stimulate apoptosis by activating and stabilizing p53, CCAR2 was initially considered to be a tumor suppressor. However, an increasing number of studies have shown that CCAR2 also functions as a tumor-promoting coregulator by activating oncogenic transcription factors and regulating the enzymatic activity of epigenetic modifiers, indicating that CCAR2 may play a dual role in cancer progression by acting as a tumor suppressor and tumor promoter. Here, we review recent progress in understanding the dual tumor-suppressing and oncogenic roles of CCAR2 in cancer. We discuss CCAR2 domain structures, its interaction partners, and the molecular mechanisms by which it regulates the activities of transcription factors and epigenetic modifiers.